Planting of Mangrove Seedlings in Pattiro Sompe Village, Sibulue Subdistrict, Bone Regency, South Sulawesi - Sabilah, Anisa Aulia (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2025)
Mangrove ecosystems provide vital ecological and social functions but are increasingly threatened by land conversion and coastal abrasion. This community service aimed to rehabilitate a degraded coastal area in Pattiro Sompe Village, Sibulue Subdistrict, Bone Regency, South Sulawesi. A participatory approach was implemented, involving local communities, academics, and local authorities. A total of 1,500 seedlings of Rhizophora sp. were planted in abandoned and unproductive shrimp ponds. The planting was conducted during low tide to ensure proper rooting in muddy substrates. The results indicated positive ecological and social outcomes. The mangrove planting helped reduce coastal erosion and initiated the restoration of the degraded shoreline. Socially, the activity raised community awareness about mangrove conservation and led to the formation of a local environmental awareness group. This program demonstrated that cross-sector collaboration can strengthen local capacity and produce sustainable impacts. Long-term monitoring and maintenance systems are necessary to ensure the continuity of rehabilitation outcomes.